An Analytical Study on Spice Market in Dhaka City Using Consumer Preference - Rahman, Md. Sajedur; Hoq, Meem Rafiul; Hossain, Md. Motahar (Asian Accounting and Auditing Advancement, 2015)
The spice market is growing since consumers are showing reluctance to go for traditional systems of processing spices. The use of processed spices is increasing both in rural and urban areas. Consumers’ growing awareness of hygienic spices and busy urban life has led to rising in branded spices consumption. The country’s processed spice market is heating up as big business houses battle to win shares in the booming market. This is growing by around 15 percent a year. A leading conglomerate ACME is set to enter the market by the end of the year and another business group, PRAN, has already made its debut. SQUARE, ACI, and BD Foods are other major players in the spice market. The broader objective of this report is to study the Spice market in Dhaka city through consumer preference. The specific objectives are to analyze the spice providers in the spice market of Bangladesh, to analyze the satisfaction level of Customers for using powder spice, to identify the problem of the spice industry in marketing the product, and find out some solutions to overcome these types of problem. This research is descriptive in nature. It has been tried to use both the primary and secondary sources of collecting information and some are to make the report presentable with as less abstraction as possible. The several approaches that are used for primary data collection are questionnaire surveys, direct observation of consumers, and opinions of different levels of the retail shops. For the questionnaire survey, it has used non-probability convenience sampling. The total sample size for the study is 100 and all of the respondents are home users in the Shyamoli area. From the survey, it is found that maximum numbers of consumers keep Radhuni spice as their first choice. The pure spice comes after that. Radhuni is the market leader because of its quality and distribution intensity. The perceived quality of Radhuni is better than other brands. The packaging of spice is satisfactory. But the satisfaction related to the availability of the spice in the overall market is poor. The case of advertisement is also the same. So it is found that out of 4P`s (Marketing Mix) product strategy is good. But pricing, promotion, and distribution strategy of spice is not satisfactory enough. In this modern and fast life when women want to save time and enjoy tasty, easier, and hygienic spices, Spice providers make the best alternative for the consumers.